Mobile Robot Object Detection Method Based on Deep Learning - Guo Yuhan (International Journal of Engineering Continuity, 2023)
The task of object detection is to accurately and efficiently identify and locate a large number of predefined categories of object instances from images. With the wide application of deep learning, the accuracy and efficiency of target detection have been greatly improved. However, deep learning-based target detection still faces challenges from key technologies such as improving and optimizing the performance of mainstream target detection algorithms, improving the detection accuracy of small target objects, realizing multi-class object detection and lightweight detection model. In response to the above challenges, based on extensive literature research, this paper analyses methods for lightweight detection models and improved detection accuracy from the perspective of YOLOv5s network structure. The problems to be solved in target detection and the future research direction are predicted and prospected.